2007
DOI: 10.1186/1472-6750-7-63
|View full text |Cite
|
Sign up to set email alerts
|

Gene knockdown by RNAi in the pea aphid Acyrthosiphon pisum

Abstract: Background: RNA interference (RNAi) is a powerful method to inhibit gene expression in a sequence specific manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
137
3
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(148 citation statements)
references
References 31 publications
3
137
3
5
Order By: Relevance
“…Aphids injected with anti-Coo2 siRNAs showed earlier mortality than control insects. 74 Microinjection of dsRNA into A. pisum, also induced mRNA degradation at about 40% for 2 targets, the Ap-crt mRNA encoding a calcium binding protein (calreticulin) and the gut specific Ap-cath-L mRNA encoding a cysteine protease, cathepsin-L. 75 Rong et al (2013) showed through dsRNA injection, that b-N-acetylglucosaminidase (LmNAG1) in Locusta migratoria plays an essential role in insect molting. 76 Microinjection of dsRNAs against actin, chitin synthase 1 and V-ATPase in the citrus mealybug, Planococcus citri, showed that the corresponding mRNAs are good targets for RNAi.…”
Section: 65mentioning
confidence: 99%
“…Aphids injected with anti-Coo2 siRNAs showed earlier mortality than control insects. 74 Microinjection of dsRNA into A. pisum, also induced mRNA degradation at about 40% for 2 targets, the Ap-crt mRNA encoding a calcium binding protein (calreticulin) and the gut specific Ap-cath-L mRNA encoding a cysteine protease, cathepsin-L. 75 Rong et al (2013) showed through dsRNA injection, that b-N-acetylglucosaminidase (LmNAG1) in Locusta migratoria plays an essential role in insect molting. 76 Microinjection of dsRNAs against actin, chitin synthase 1 and V-ATPase in the citrus mealybug, Planococcus citri, showed that the corresponding mRNAs are good targets for RNAi.…”
Section: 65mentioning
confidence: 99%
“…Successful results were obtained in preventing bee mortality by Israeli Acute Paralysis Virus Disease (IAPV) infection under natural beekeeping conditions (Hunter et al, 2010), but many efforts focused on the possibility to control insect pests by means of RNAi. For these studies different insect models were used, such as Drosophila melanongaster Meigen (Misquitta & Paterson, 1999;Dzitoyeva et al, 2001;Schmid et al, 2002), Tribolium castaneum (Herbst) (Bucher et al, 2002;Tomoyasu & Denell, 2004;Tomayasu et al, 2008), honeybees (Amdam et al, 2003), Acyrthosiphon pisum (Harris) (Mutti et al, 2006;Jaubert-Possamai et al, 2007), the green peach aphid Myzus persicae Sulzer (Pitino et al, 2011), the western corn rootworm Diabrotica virginifera virginifera (LeCompte) (Baum et al, 2007;Alves et al, 2010). In almost all the experiments carried out, dsRNA was injected directly in the organism, but this kind of dsRNA delivery is not feasible in the protection of crops against phytophagous insects.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…MpC002 is predominantly expressed in the M. persicae salivary glands and transient over-expression of MpC002 in Nicotiana benthamiana improved M. persicae fecundity [13]. Microinjection of long dsRNA into A. pisum also leads to silencing of genes encoding calreticulin and cathepsin by 30-40% [11]. Calreticulin is a calcium-binding protein that is produced in most aphid tissues, while cathepsin is specifically produced in the pea aphid gut.…”
Section: Introductionmentioning
confidence: 99%
“…Calreticulin is a calcium-binding protein that is produced in most aphid tissues, while cathepsin is specifically produced in the pea aphid gut. Thus, gene silencing appears to occur in different aphid tissues [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation